The Higher-Ed Organizational-Scholar Tension: How Scholarship Compatibility and the Alignment of Organizational and Faculty Skills, Values and Support Affects Scholar's Performance and Well-Being - Pereyra-Rojas, Milagros; Mu, Enrique; Gaskin, James; Lingham, Tony (Frontiers in Psychology, 2017)
Scholars and institutions alike are concerned with academic productivity. Scholars not only further knowledge in their professional fields, they also bring visibility and prestige to themselves and their institutions, which in turn attracts research grants and more qualified faculty and graduate students. Many studies have been done on scholar productivity, and many of them focus on individual factors such as gender, marital status, and individual psychological characteristics. Also, a few studies are concerned about scholars’ well-being. We propose a causal model that considers the compatibility of the scholarship dimensions valued by scholars and institutions and their academic alignment with actual institutional recognition and support. We test our causal model with data from a survey of 803 faculty participants. Our findings shed light on how the above academic factors affect not just academic productivity but also a scholar’s well-being. Importantly, we show that academic alignment plays a crucial mediating role when predicting productivity and well-being. These results have important implications for university administrators who develop, and faculty who work under, policies designed to foster professional development and scholarship.